1997
DOI: 10.1038/sj.onc.1201016
|View full text |Cite
|
Sign up to set email alerts
|

The expression of RET and its multiple splice forms in developing human kidney

Abstract: A series of inductive events between two di erent cell groups, the ureteric bud epithelium and metanephric mesenchyme, gives rise to the functional mammalian kidney. These reciprocal inductive interactions involve a number of molecules, one of which is the RET receptor tyrosine kinase. The phenotype of mice lacking functional RET includes kidney agenesis or severe dysgenesis, indicating a requirement for RET in kidney organogenesis. To investigate RET expression in human kidney development, we used a semi-quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Recently, c-ret transcripts were detected in the adult human kidney (Ivanchuk et al, 1997) and we also found expression in adult mouse kidneys by RT ± PCR. Using in situ hybridization, we found ubiquitous localization of the transcript in the adult kidney.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Recently, c-ret transcripts were detected in the adult human kidney (Ivanchuk et al, 1997) and we also found expression in adult mouse kidneys by RT ± PCR. Using in situ hybridization, we found ubiquitous localization of the transcript in the adult kidney.…”
Section: Discussionsupporting
confidence: 63%
“…Although RET was not detected in adult rat kidneys, alternative spliced transcripts were detected in the adult human kidney by using reverse transcription-polymerase chain reaction (RT ± PCR; Ivanchuk et al, 1997). Here we report the study of c-ret expression in embryonic, neonatal (day 7) and adult mouse kidneys.…”
mentioning
confidence: 95%
“…RET is expressed in cells and tissues derived from the neural crest, branchial arches and kidney (Pachnis et al, 1993;Tahira et al, 1990). Expression is highest in early developmental stages decreasing to low adult levels (Avantaggiato et al, 1994;Durbec et al, 1996b;Ivanchuk et al, 1997;Pachnis et al, 1993). In situ hybridization studies have localized RET expression to the ureteric bud in embryonic murine kidney (Pachnis et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…RET encodes multiple transcripts resulting from alternative splicing of 5' or 3' exons (Ivanchuk et al, 1997;Lorenzo et al, 1995;Myers et al, 1995;Tahira et al, 1990). Skipping of exons encoding the RET extracellular domain results in products with deletions within the putative ligand binding portion of the receptor or in a truncated soluble isoform (Ivanchuk et al, 1997;Lorenzo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation